Consumer Sensory Evaluation of Ground Beef and Plant-Based Ground Beef Alternatives Used in a Taco Application - L. A. Egger; K. J. Farmer; E. S. Beyer; K. R. Lybarger; J. L. Vipham; M. D. Zumbaugh; M. D. Chao; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to evaluate consumer preferences for palatability traits and consumer acceptability of three plant-based protein alternatives and ground beef in a taco application. Study Description:Three commercially available plant-based ground beef alternative (GBA) treatments (n = 20) were selected based upon industry prevalence. The GBAs’ were identified as the most popular in the marketing sectors of foodservice (FGBA), retail (RGBA), and traditional (TGBA). One ground beef (80% lean; 20% fat) treatment (n = 20) was selected. Samples were crumbled into a skillet and cooked to a surface temperature of 180°F. Following cooking, a generic taco seasoning was added following manufacturer’s instruction. Samples were served on a flour tortilla with the opportunity to add cheese, lettuce, and tomatoes. The Bottom Line:This research indicates consumers preferred ground beef to ground beef alternatives when used as a crumbled protein ingredient in tacos.Ground beef should be marketed as a distinct eating experience to consumers at foodservice and retail when plant-based ground beef alternatives are available in similar crumbled products.
Keywords: consumer; ground beef; ground beef alternatives